Nursing students and COVID-19 vaccination. ESitA Study An Observational Study - Pierini, Elisa; Giusti, Gian Domenico; Gili, Alessio; De Laurentiis, Oliver Nicola; Ramacciati, Nicola (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Vaccine hesitancy is an important problem in terms of health policy. This historical moment leads us to wonder if vaccine hesitancy is also present among nursing students who should be particularly sensitive to the subject Methods: Between February 10 to February 17 2021, 1080 students enrolled in the Bachelor of Science in Nursing in the Department of Medicine and Surgery of the University of Perugia, were invited to reply to an online questionnaire sent to their university email accounts. Results and Conclusions: A certain amount of vaccination hesitancy was detected among the students in our study. It can be assumed that the issues surrounding the AstraZeneca vaccine, which occurred at the start of the vaccination campaign, may have led to an increase in people’s hesitancy. Boosting vaccination campaigns, including appropriate use of social media, may lead to greater acceptance. Also, it would be useful to assess the cultural basis of the recent anti-Vax controversy, particularly for students of nursing or other health professions, who should be able to evaluate, source and recognize the most validated data.